Nickel-catalyzed regioselective C(2)-H difluoroalkylation of indoles with difluoroalkyl bromides - Soni, Vineeta; Sharma, Dipesh M.; Punji, Benudhar (Chemistry-An Asian Journal, 2018)
Regioselective C(2)-H difluoroalkylation of C-3 unsubstituted indoles with commonly available fluoroalkyl bromides is successfully achieved employing a simple nickel catalyst system, (DME)NiCl2/Xantphos. This methodology shows excellent regioselectivity and exhibits a broad substrate scope. Various functional groups, such as -OMe, -F, and -Br, are tolerated on the indole backbone to give the difluoroalkylated products in moderate to good yields. Preliminary mechanistic findings demonstrate that the reaction is homogeneous in nature and involves a radical manifold. Synthetic utility of this nickel-catalyzed method is demonstrated by synthesizing melatonin receptor antagonist Luzindole derivative.